Formation and Stability of Low‐Dimensional Structures for Group VIIIB and IB Transition Metals: The Role of sd4 Hybridization. Issue 4 (21st January 2016) - Yang, Jianhui; Zhang, Qiuju; Chen, Liang; Wang, Gang; Chen, Xiaolong
Abstract : A quasi‐sd 4 hybridization state for group VIIIB and IB face‐centered cubic (FCC) transition metals in low‐dimensional nanostructures is identified, in contrast to the sd 5 hybridization state in bulk. For Au, a novel three‐shelled nanowire is designed with a hexagonal close‐packed core in the sd 5 hybridization, wrapped by FCC‐(111) shell that adopts the quasi‐sd 4 hybridization. This new nanostructure exhibits remarkable stability and electronic properties.